Tales in social practices of nature worshippers of Western Slovenia - Toplak, Cirila (Acta Histriae, 2022)
In this scientific article, the historical counterculture of Nature Worshippers in Western Slovenia is explained with emphasis on social functions of their oral tradition i.e. tales. The latter, recorded and published primarily by Pavel Medvešček – Klančar, were an important part of Nature Worshippers’ educational concept. Cosmogonic myths, etiological explanations, animal tales and anecdotes introduced young children to the ethical norms and spiritual life of the community and played an important role in preserving the identity of Nature Worshippers. Detailed contextual and sociological analysis of Nature Worshippers’ tales focuses on Pavel Medvešček’s 1991 collection On a Red Cloud a Vineyard Grows and his 2015 book From the Invisible Side of the Sky. Revealed Secrets of the Old Belief
Keywords: naravoverstvo; Pavel Medvešček – Klančar; pravce; Pravljice; Rodnoverstvo; Vzgoja in izobraževanje